The Effect of Water Chemistry on Thermochemical Sulfate Reduction: A Case Study from the Ordovician in the Tazhong Area, Northwest China. (15th October 2017) - Li, Hongxia; Cai, Chunfang; Jia, Lianqi; Xu, Chenlu; Zhang, Ke
Abstract : Formation water chemistry, sulfate sulfur isotopes, and associated H2 S contents and sulfur isotopes were measured from the Ordovician in Tazhong area, Tarim Basin. The aim is to elucidate the effects of geochemical composition of formation water on thermochemical sulfate reduction (TSR) and potential usage of SO4 /Cl ratios as a new proxy for TSR extents in areas, where H2 S and thiaadamantanes (TAs) data are not available. The formation water has SO4 /Cl ratios from 0.0002 to 0.016, significantly lower than 0.04 to 0.05 from 3 to 7 times evapoconcentrated seawater. Thus, the low values are explained to result from TSR. Furthermore, the SO4 /Cl ratios show negative correlation relationships to TAs and H2 S concentrations, indicating that TSR occurred in a relatively closed system and SO4 /Cl ratio can be used to indicate TSR extents in this area. Extensive TSR in the Cambrian in the Tazhong area, represented by low SO4 /Cl ratios and high H2 S and TAs concentrations, is accompanied by formation water with high TDS and Mg concentrations, indicating the effects of water chemistry on TSR under a realistic geological background. In contrast, the low TSR extent in the Ordovician may have resulted from limited TSR reaction duration and total contribution of aqueous S O 4 2 - .